1997
DOI: 10.1046/j.1365-3024.1997.d01-186.x
|View full text |Cite
|
Sign up to set email alerts
|

The isolation of a 22 kDa band after SDS‐PAGE of Schistosoma mansoni adult worms and its use to demonstrate that IgE responses against the antigen(s) it contains are associated with human resistance to reinfection

Abstract: In schistosomiasis endemic areas, intensities of reinfection after treatment are greater amongst young children than amongst adults, and high levels of parasite-specific IgE are associated with resistance to reinfection in an age-dependent manner. Previously we have reported that, in Western blots, a 22 kDa band was recognized by human IgE and that the incidence and intensity of S. mansoni reinfection were significantly lower amongst individuals who had IgE against this band, compared with those who did not (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 32 publications
2
58
1
Order By: Relevance
“…The evidence that antibody responses to the three TALs are boosted when worms are killed by chemotherapy (11) supports this conclusion. Previous studies have correlated TAL1 IgE with resistance to reinfection (8,9,20,28), but this association was not significant in the current study. The response to worm antigen TAL1 is likely to be a marker for protective responses rather than protective in itself, and factors such as environmental and behavioral heterogeneity may mask the association with immunity in some studies (20).…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The evidence that antibody responses to the three TALs are boosted when worms are killed by chemotherapy (11) supports this conclusion. Previous studies have correlated TAL1 IgE with resistance to reinfection (8,9,20,28), but this association was not significant in the current study. The response to worm antigen TAL1 is likely to be a marker for protective responses rather than protective in itself, and factors such as environmental and behavioral heterogeneity may mask the association with immunity in some studies (20).…”
Section: Discussioncontrasting
confidence: 92%
“…Dunne et al reported that the dominant IgE antigen in S. mansoni is tegumental-allergen-like protein-1 (TAL1). Also known as Sm22.6, it is a molecule from the outer, tegumental layer of both schistosomula and adult worms (9,25), and the IgE response to TAL1 has been associated with resistance to reinfection in studies in Kenya and Uganda (8,9,20,28). The molecule is a member of a family of 13 developmentally expressed tegumental proteins (TAL1 to TAL13) (11,12).…”
mentioning
confidence: 99%
“…Several reports have documented an association between IgE responses to schistosome antigens and resistance to reinfection, mostly in young individuals (12,15,16,24,30,39). Other reports and ours are not consistent with this view, possibly because of the difference in the age range of the individuals examined (38).…”
Section: Discussionmentioning
confidence: 99%
“…The methods used for preparation of S. mansoni soluble worm antigen (SWA) and crude P. falciparum schizont antigen have been described previously (7,25). Specific levels of IgG1, IgG3, and IgG4 against SEA, SWA, and Pfs were determined by enzyme-linked immunosorbent assays (ELISA), as described previously (25).…”
Section: Methodsmentioning
confidence: 99%